(−)-9′-O-(α-l-Rhamnopyranosyl)lyoniresinol from Lespedeza cuneata suppresses ovarian cancer cell proliferation through induction of apoptosis. Issue 2 (15th January 2018) - Baek, Jiwon; Lee, Dahae; Lee, Tae Kyoung; Song, Ji Hoon; Lee, Ju Sung; Lee, Seong; Yoo, Sang-Woo; Kang, Ki Sung; Moon, Eunjung; Lee, Sanghyun; Kim, Ki Hyun
Graphical abstract: Abstract: Lespedeza cuneata (Dum. Cours.) G. Don. (Fabaceae), known as Chinese bushclover or sericea lespedeza, has been used in traditional medicine to treat diabetes, hematuria, and insomnia, and it has been reported that bioactive compounds from L. cuneata possess various pharmacological properties. However, there has been no study to determine the active compounds from L. cuneata with potential activity against ovarian cancer. This study aimed to isolate cytotoxic compounds from L. cuneata and identify the molecular mechanisms underlying the apoptosis pathway in ovarian cancer cells. Based on cytotoxic activity identified in the screening test, chemical investigation of the active fraction of L. cuneata led to the isolation of nine compounds including four lignanosides (1 –4 ), three flavonoid glycosides (5 –7 ), and two phenolics (8 –9 ). Cytotoxicity and the molecular mechanism were examined by methyl thiazolyl tetrazolium (MTT) assay and Western blot analysis. Of the isolated compounds, (−)-9′- O -(α-l -rhamnopyranosyl)lyoniresinol (3 ) demonstrated the strongest effect in suppressing A2780 human ovarian carcinoma cell proliferation in a dose-dependent manner, with an IC50 value of 35.40 ± 2.78 μM. Control A2780 cells had normal morphology, whereas cell blebbing, shrinkage, and condensation were observed after treatment with compound3 . Western blotting analysis showed that compound3 inhibited A2780 human ovarian cancer cell viability by activating caspase-8, caspase-3, and PARP, which contributed to apoptotic cell death. These results suggest that (−)-9′- O -(α-l -rhamnopyranosyl)lyoniresinol (3 ) has potent anticancer activities against A2780 human ovarian carcinoma cells through the extrinsic apoptotic pathway. Therefore, (−)-9′- O -(α-l -rhamnopyranosyl)lyoniresinol is an excellent candidate for the development of novel chemotherapeutics.